Determinant of Risk Financing in Peer-To-Peer Lending on Sharia Perspective - Izzun Khoirun Nissa; Moch. Taufiq Nur Sapto W; Rahid Kurnia; Roby Kurniadinata (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This paper aims to discuss the implementation of sharia fintech financing and risks that have the potential to occur in Indonesia. Fintech operational activities sharia with a peer-to-peer (P2P) financing model and risk mitigation can carried out to minimize the risks in Indonesia that make MSMEs as the main market segment. This paper discusses the development of sharia fintech in Indonesia and more specifically its contribution nationally. Case studies are derived from Wrong One platforms P2P Which Once get award as The best Sharia fintech in providing services to MSMEs in Indonesia. Finally, will closed with resolution sharia in finish financing problematic. This paper contributes to the development of sharia fintech Because give description difference risks fintech sharia with other sharia financial institutions because sharia fintech places more emphasis on risk sharing and not making financial intermediation institutions the only the only one risk bearer greatest liquidity.